Nutrition-sensitive value chains: A guide for project design. Volume I - Peña, Isabel de la; Garrett, James (International Fund for Agricultural Development, 2018)
This publication, Nutrition-sensitive value chains: A guide for project design has been produced to fill a key knowledge gap in the emerging field of value chains for nutrition by providing guidance on how to design nutrition-sensitive value chain (NSVC) projects, with a particular focus on smallholder producers. The participatory and consultative approach taken for the development of this guide, which has been field-tested in Nigeria and Indonesia and subject to wide expert consultations at country and global levels, has been instrumental in ensuring voices and practical experiences from the field are adequately reflected. The approach that has emerged from these experiences is one that shifts from the traditional value chain approach of focusing on demand alone, to one that starts by understanding the nutrition needs of consumers in order to identify investments that can improve diets while remaining economically viable and addressing issues of environmental sustainability and empowerment of women.